Analisis Manajemen Stres pada Fenomena Quiet Quitting: Studi Literatur Mahasiswa Generasi Z - Ashri Andini Muthmainnah; Raisha Ramadhani; Widuri Dwi Nanda; Sri Mulyeni (Jurnal Manajemen Kewirausahaan dan Teknologi, 2026)
The phenomenon of academic quiet quitting is currently widespread among Generation Z students as an adaptive response to excessive workloads that trigger mental exhaustion. This study aims to analyze the effectiveness of stress management in addressing academic quiet quitting tendencies among university students. The method used is a literature study with content analysis techniques on various scientific articles from databases such as Google Scholar within the last few years. The results indicate that the majority of students experience moderate academic stress, which significantly reduces active participation and disrupts physical well-being, including decreased sleep quality. Furthermore, a positive correlation was found where good stress management skills can significantly increase learning motivation and strengthen student mental resilience in facing pressure. In conclusion, stress management skills are vital instruments that must be integrated into the educational ecosystem through institutional support and empathic leadership to rebuild student commitment and professional readiness sustainably.